Process for conducting resource recycling on copper and arsenic from arsenic-containing waste acid - FANG DUAN (2016)
The invention discloses a process for conducting resource recycling on copper and arsenic from arsenic-containing waste acid. Resource recycling of the arsenic-containing waste acid is realized through the steps of neutralization and impurity removal, arsenic precipitation, washing, leaching, evaporation crystallization and preparation of arsenic trioxide through dissolution. According to the process, arsenic in the arsenic-containing waste acid is precipitated, converted and prepared into arsenic trioxide, and the defects of preparing arsenic trioxide by reducing copper arsenite with sulfur dioxide are overcome; high-standard arsenic trioxide is obtained, and treatment of the waste acid and reutilization of copper and arsenic resources are realized. 本发明公开种含砷污酸资源化回收铜和砷的工艺，通过中和除杂-沉砷-洗涤-浸出-蒸发结晶-溶解制取三氧化二砷，实现含砷污酸的资源化。本发明将含砷污酸中的砷经过沉淀转化制备成三氧化二砷，克服二氧化硫还原亚砷酸铜制备三氧化二砷的缺点，并且得到高标准的三氧化二砷，实现污酸的治理及铜砷资源的再利用。